A build surface study of Powder-Bed Electron Beam Additive Manufacturing by 3D thermo-fluid simulation and white-light interferometry. (October 2017) - Shrestha, Subin; Chou, Kevin
Abstract: In this study, a three dimensional (3D) thermo-fluid model for the Powder Bed Electron Beam Additive Manufacturing (PB-EBAM) process was developed using ANSYS FLUENT software. Temperature dependence of both the surface tension and material physical properties was incorporated. In addition, the melt-pool free-surface dynamics was established using the volume of fluid (VOF) approach, taking into account the energy, volume fraction and flow equations at the interface when heated by a moving heat source. The developed model was applied to study the beam speed effect in the raster scanning scenario. In addition, the surfaces of PB-EBAM-fabricated Ti-6Al-4V parts were analyzed using a white-light interferometer. The results show that, in general the build surface roughness along the beam moving direction slightly increases with the scanning speed. On the other hand, the hatch spacing noticeably affects the surface roughness in the transverse direction. The experimentally acquired average surface roughness increased from about 3 µm for lower speed about 483 mm/s to 11 µm for higher speed case about 1193 mm/s. In addition, the average roughness of 4.28 µm, 5.5 µm, and 9.84 µm were obtained from simulation for different beam speeds which shows similar trend as that of experiment. Highlights: A 3D free surface model has been developed for Powder-Bed Electron Beam Additive Manufacturing (PB-EBAM) process. Surface formation at different beam speed is studied experimentally and numerically. Surface roughness in transverse direction is greater than scanning direction. At low speed, a semi-periodic wave is formed in transverse direction which is function of hatch spacing. Surface roughness in PB-EBAM process increases with speed which is observed both experimentally and numerically.